TECHNOLOGY ACCEPTANCE OF THE POWER OUTAGE COMPLAINT REPORTING FEATURE ON "NEW PLN MOBILE" APPLICATION - Satria Prasamya; Muh. Asdar; Haeriah Hakim (Paulus Journal of Accounting (PJA), 2023)
This study aims to measure the level of technology acceptance of the outage reporting feature in the "New PLN Mobile" application. This research will be conducted at PT PLN UP03 South Makassar working area. Where the sample in this study were users of the New PLN Mobile application who live in the work area of the object under study. Furthermore, this research is a quantitative descriptive study with the aim of analyzing in depth the technological acceptance of the outage reporting feature in the "New PLN Mobile" application using the Technology Acceptance Model (TAM) framework. The results showed that there are four measurement dimensionsused in this study, namely perceived usefulness, perceived ease of use, intention to use and actual use. The majority of measurement indicators are categorized as excellent. However, there is one measurement indicator that is not appropriate when applied to the object of this research, namely the number of reports that have been successfully sent as one of the measurement indicators of actual use is not appropriate to use on the object of research if it is based on how often someone sends a complaint (this is suitable for high- frequency transactions such as the banking service sector).